Intravenous Fluid Administration and the Coagulation System - Boyd, Corrin J.; Brainard, Benjamin M.; Smart, Lisa (Frontiers in Veterinary Science, 2021)
Intravenous fluid administration in veterinary patients can alter coagulation function by several mechanisms. Both crystalloid and colloid fluids cause hemodilution, reducing platelet count and plasma coagulation protein concentrations. Hemodilution is associated with a hypercoagulable effect at low dilutions and a hypocoagulable effect at higher dilutions. Composition of crystalloid fluids likely has a minor effect, primarily dependent on fluid ion composition. Hypertonic crystalloids may also cause hypocoagulability. Colloids, both synthetic and natural, can cause hypocoagulability by several mechanisms beyond the effects of hemodilution. These include impaired platelet function, decreased plasma coagulation factor activity, impaired fibrin formation and crosslinking, and accelerated fibrinolysis. The vast majority of the veterinary literature investigates the hypocoagulable effects of hydroxyethyl starch-containing fluids using in vitro, experimental, and clinical studies. However, results are inconsistent, likely due to the varying doses and physicochemical properties of the specific fluid products across studies. In addition, some evidence exists for hypocoagulable effects of gelatin and albumin solutions. There is also evidence that these colloids increase the risk of clinical bleeding in people. Limitations of the veterinary evidence for the hypocoagulable effects of colloid fluids include a predominance of in vitro studies and in vivo studies using healthy subjects, which exclude the interaction of the effects of illness. Therefore, clinical relevance of these effects, especially for low molecular weight hydroxyethyl starch, is unknown. Firm recommendations about the most appropriate fluid to use in clinical scenarios cannot be made, though it is prudent to limit the dose of synthetic colloid in at-risk patients. Clinicians should closely monitor relevant coagulation assays and for evidence of hemorrhage in at-risk patients receiving any type of fluid therapy, especially in large volumes.